First white-flowered species of Sertifera (Orchidaceae) discovered in Colombia - Szlachetko, Dariusz L.; Kolanowska, Marta; Medina Trejo, Ramiro (Biodiversity: Research and Conservation, 2015)
A new species of Sertifera is described and illustrated based on Colombian material. The novelty resembles Sertifera colombiana, but it is characterized by glandular leaf sheaths, larger, white flowers, ovate to oblong-ovate sepals, ligulatelanceolate petals and apically triangular lip. This is the first report of a white-flowered representative of the genus.